KEBERSYUKURAN UNTUK MENINGKATKAN KESEJAHTERAAN PADA WANITA KORBAN PELECEHAN SEKSUAL - Wijaya, Yenny Duriana; Widiastuti, Mariyana (Jurnal Psikologi : Media Ilmiah Psikologi, 2019)
The purpose of the study was to determine the effectiveness of the gratitude intervention to improve subjective welfare for victims of sexual abuse. Many of the effects of sexual abuse include low of self-confidence,low of self-esteem, depression, anxiety, fear of rape and increased fear of other criminal acts. This condition causes the woman becoma low of well being , which tends to feel dissatisfied with their lives, does not feel happiness and often feels negative emotions such as anxiety and anger. Therefore, it is necessary to handle efforts so that victims of sexual abuse can improve their welfare. One way that can be done is to provide a gratitude intervention. Gratitude is the construction of cognitive, emotional, and behavioral. Gratitude as cognitive construction is shown by recognizing the generosity and kindness of the blessings that have been received and focusing on the positive things in him today. As an emotional construction, gratitude is characterized by the ability to change the emotional response to an event so that it becomes more meaningful. Quantitative data analysis using nonparametric Wilcoxon Signed Ranks Test. Qualitative data analysis from observations and interviews. The result of data analysis shows that the probability is 0.021, this value indicates that the probability is below 0.05. So it can be concluded that the gratitude intervention can improve subjective well-being of sexually abused victim Keywords: Gratitude, subjective well-being, women victims of sexual abuse